Very strong trans effect in ruthenacyclic carbamoyl complexes leads to ligand redistribution in phosphine derivatives - Barik, Chandan Kr (2020)
The ruthenacyclic carbamoyl complexes [Ru (2-NHC(O)C5H4N) (CO)2(X) (NCMe)] (X = Cl, Br) (1) and [Ru (2-NHC(O)C5H4N) (CO)2 (2-S-Py)] (2) undergo substitution reactions with organophosphines to afford derivatives which are prone to a redistribution of the phosphine ligand. We have studied these redistribution reactions experimentally and computationally, and proposed an essentially common reaction pathway. The results suggest that the carbamoyl ligand exerts a very strong trans effect.